2020
DOI: 10.1016/j.ebiom.2020.102845
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale regulation of L-type calcium channels differentiates between ischemic and dilated cardiomyopathies.

Abstract: Background: Subcellular localization and function of L-type calcium channels (LTCCs) play an important role in regulating contraction of cardiomyocytes. Understanding how this is affected by the disruption of transverse tubules during heart failure could lead to new insights into the disease. Methods: Cardiomyocytes were isolated from healthy donor hearts, as well as from patients with cardiomyopathies and with left ventricular assist devices. Scanning ion conductance and confocal microscopy was used to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…4 c–f). Such differences in the local control of LTCC activity have been previously reported for the failing LVMs, mostly for the crest membrane fraction of LTCC 11 , 33 , but also for the T-tubule fraction in ischemic cardiomyopathy 23 . In myocytes, AKAP5 was shown to organise the signalling pathway following sympathetic stimulation by targeting adenylyl cyclase, PKA and calcineurin to a specific subpopulation of LTCC 34 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…4 c–f). Such differences in the local control of LTCC activity have been previously reported for the failing LVMs, mostly for the crest membrane fraction of LTCC 11 , 33 , but also for the T-tubule fraction in ischemic cardiomyopathy 23 . In myocytes, AKAP5 was shown to organise the signalling pathway following sympathetic stimulation by targeting adenylyl cyclase, PKA and calcineurin to a specific subpopulation of LTCC 34 .…”
Section: Discussionsupporting
confidence: 58%
“…Increase in LTCC Po has been linked to channel phosphorylation, and PKA was shown to be one of the main phosphorylation agents of Ca 2+ handling proteins, including LTCC 21 , 22 . A recent study of human LVMs from ischemic cardiomyopathy hearts showed that the hyperactive T-tubule anchored LTCCs can be phosphorylated by PKA 23 . To assess if PKA is involved in the elevated Po observed in T-tubule LTCC in MI RVM, we used H89 as a PKA blocker.…”
Section: Resultsmentioning
confidence: 99%
“…51 Indeed, it is beginning to emerge that cAMP-mediated signalling occurs within defined intracellular nano-scale compartments, [52][53][54] enabling even multiple cellular responses to occur simultaneously. [55][56][57][58] The interplay of cAMP synthesis and degradation by the constitutively active and strategically positioned PDEs establishes gradients and local pools of cAMP that are sensed by cAMP effectors located at defined cellular compartments. The formation of the gradients involves the "buffering" of cAMP, that is, binding to targets to slow diffusion; otherwise synthesis would exceed PDEs' hydrolysis capacity and cAMP would evenly flood the cells.…”
Section: Compartmentalization Of Camp Signallingmentioning
confidence: 99%
“…Adrenomedullin acts through a phospholipase C pathway involving protein kinase C. A likely explanation for these opposite effects is that different pools of cAMP are activated by the two receptors 51 . Indeed, it is beginning to emerge that cAMP‐mediated signalling occurs within defined intracellular nano‐scale compartments, 52‐54 enabling even multiple cellular responses to occur simultaneously 55‐58 …”
Section: The Compartmentalization Of Camp Signallingmentioning
confidence: 99%
“…As part of this process, abnormal expression and distribution of connexins alter gap junction function and further compromise electrical conduction [ 12 ]. Impaired calcium signaling is a hallmark finding in heart failure at the cellular level, with post-MI remodeling associated with distinct features describing the spatial location and function of L-type calcium channels [ 13 ]. Therefore, calcium sparks, manifesting as early or delayed afterdepolarizations, constitute an additional arrhythmogenic mechanism in post-MI heart failure [ 14 ].…”
Section: Ventricular Remodeling Post-mimentioning
confidence: 99%